Current Understanding of Leukocyte Phenotypic and Functional Modulation During Extracorporeal Membrane Oxygenation: A Narrative Review - Ki, Katrina K.; Millar, Jonathan E.; Langguth, Daman; Passmore, Margaret R.; McDonald, Charles I.; Shekar, Kiran; Shankar-Hari, Manu; Cho, Hwa Jin; Suen, Jacky Y.; Fraser, John F. (Frontiers in Immunology, 2021)
acute respiratory distress syndrome and cardiogenic shock, which potentially require extracorporeal membrane oxygenation (ECMO) support, are associated with changes in leukocyte numbers, phenotype and functions. The changes observed in these illnesses could be compounded by exposure of blood to the non-endothelialised surfaces and non-physiological conditions of ECMO. This can result in further leukocyte activation, increased platelet-leukocyte interplay, pro-inflammatory and pro-coagulant state, alongside features of immunosuppression. However, the effects of ECMO on leukocytes, in particular their phenotypic and functional signatures, remain largely overlooked, including whether these changes have attributable mortality and morbidity. The aim of our narrative review is to highlight the importance of studying leukocyte signatures to better understand the development of complications associated with ECMO. Increased knowledge and appreciation of their probable role in ECMO-related adverse events may assist in guiding the design and establishment of targeted preventative actions.